Optimal glycated hemoglobin A1c value for prediabetes and diabetes in patients with pancreatic diseases - Chen, Guanhua; Zhang, Rui; Tan, Chunlu; Liu, Xubao; Yu, Lei; Chen, Yonghua (Frontiers in Endocrinology, 2023)
Background Some articles suggest that using HbA1c alone for diabetes diagnosis is inappropriate. It requires considerable researches to explore the efficacy of HbA1c for diagnosing hyperglycemia in patients with pancreatic disease. Methods This study analyzed 732 patients, comprising of 331 without pancreatic disease and 401 patients diagnosed with pancreatic diseases. All participants underwent the HbA1c assay and oral glucose tolerance test. Kappa coefficients were calculated to assess agreement between the HbA1c and glucose criteria. The receiver operating characteristic curve (ROC) was used to calculate the optimal HbA1c value. DeLong test was analyzed to compared the aera under curves (AUCs) Results There were 203 (61.3%) patients with NGT, 78 (23.6%) with prediabetes, and 50 (15.1%) with diabetes in patients without pancreatic diseases. In patients with pancreatic disease, 106 participants were diagnosed with NGT (36.4%), 125 with prediabetes (31.2%), and 130 with diabetes (32.4%). Patients with pancreatic disease exhibited elevated levels of bilirubin, transaminase enzymes, aspartate transaminase, high density lipoprotein cholesterol and total bile acid. The sensitivity and specificity of the HbA1c (6.5%) for diagnosing pancreatic diabetes were 60.8% (95% CI 52.3, 69.3) and 92.6% (95% CI 89.5, 95.7). In prediabetes, the sensitivity and specificity of HbA1c (5.7%) is 53.2% (44.3, 62.0) and 59.6 (51.5, 67.6). The optimal HbA1c value for diagnosing diabetes was 6.0% (AUC = 0.876, 95% CI 0.839, 0.906), with the sensitivity of 83.8% and the specificity of 76.8%. The optimal HbA1c value for the diagnosis of prediabetes was 5.8% (AUC = 0.617, 95% CI: 0.556, 0.675), with the corresponding sensitivity and specificity of 48.0% and 72.6% respectively. The combined tests (HbA1c, 6.0% or FPG, 7.0mmol/L) presented the sensitivity of 85.7% （95% CI 79.1, 91.3）and the specificity of 92.6% (95% CI 87.6, 97.3) in pancreatic diabetes. Conclusions: From our results, the recommended HbA1c by ADA criterion may not be sufficiently sensitive to diagnose hyperglycemia in pancreatic disease. The optimal value of 5.8% and 6.0% improved the accuracy for diagnosing prediabetes and diabetes and should be considered to be applied. Besides, we advocate the combination of HbA1c and FPG test for the diagnosis of diabetes in patients with pancreatic diseases.